Comparative study of orthopaedic trauma pattern in covid lockdown versus non-covid period in a tertiary care centre - Bhat, Anil K. (J Orthop, 2020)
OBJECTIVES: Patterns of trauma during the covid-19 lockdown were reviewed. METHODS: Epidemiological factors, mechanism and pattern of injuries of 235 patients during the lockdown were compared with 627 patients during similar time frame in 2019. Protocols followed in treating these patients were reviewed. RESULTS: Significant increase were noted in domestic injuries due to slip and fall at home, fall from height, trees, snake bite and hip and spine fractures during the lockdown. CONCLUSION: Though the type of injuries during the lockdown were different, they warrant treatment on urgent basis even during the covid times to avoid long term morbidity.